2015
DOI: 10.1186/s12944-015-0102-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of cholesterol absorption gene Numb polymorphism with Coronary Artery Disease among Han Chinese and Uighur Chinese in Xinjiang, China

Abstract: BackgroundHypercholesterolemia is a major risk factor for coronary artery disease (CAD). As Numb is an important regulating factor for intestinal cholesterol absorption and plasma cholesterol level, the aim of the present study is to assess the association between human Numb gene polymorphism and CAD among Han and Uighur Chinese.MethodsWe have conducted two independent case–control studies in Han Chinese (384 CAD patients and 433 controls) and Uighur Chinese (506 CAD patients and 351 controls) subjects. All su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Dyslipidemia is the second leading cause of cardiovascular disease-related death after hypertension [ 23 ]. The prevalence of hypertension plus dyslipidemia and overweight/obesity was reportedly high in Xinjiang [ 16 , 28 ] and we made similar observations in the course of this study. Indeed, we also observed that the levels of BMI and LDL-C in hypertensive patients were close to levels of hypertensive patients in the United States [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Dyslipidemia is the second leading cause of cardiovascular disease-related death after hypertension [ 23 ]. The prevalence of hypertension plus dyslipidemia and overweight/obesity was reportedly high in Xinjiang [ 16 , 28 ] and we made similar observations in the course of this study. Indeed, we also observed that the levels of BMI and LDL-C in hypertensive patients were close to levels of hypertensive patients in the United States [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it has also been directly implicated in the control of circulating cholesterol levels through its role in regulating intestinal cholesterol absorption (27,44). A recent study reported that genetic variants in Numb may be associated with coronary artery disease in humans (1). Furthermore, it is worth noting that TMAO feeding has been shown to cause a decrease in cholesterol absorption and in Niemann-Pick C1-like1 (Npc1L1) abundance, which interacts with Numb during Clathrin-mediated cholesterol absorption in the intestine (23, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting correlation is between TNNT1 variations, HDL levels, and coronary artery disease [15]. Finally, it has been suggested that Numb gene haplotypes, the regulating factor for intestinal cholesterol absorption and plasma cholesterol level, are related to coronary artery disease in Han Chinese [18].…”
Section: Dyslipidemiamentioning
confidence: 98%